ความชุกและปัจจัยที่เกี่ยวข้องกับการเกิดผื่นผิวหนังอักเสบบริเวณมือของพนักงานทำความสะอาดในบริษัทรับจ้างทำความสะอาดแห่งหนึ่งในกรุงเทพมหานคร - รชยา หาญธัญพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The aim of this study was to determine the prevalence and associated factors of hand dermatitis among cleaners at a cleansing service company. A cross-sectional survey was conducted during April , 2008. Data were collected from a sample of 552 cleaners aged ≥ 18 years by a self – administrated questionnaire, and physical examination for those who have history of hand dermatitis. Totally 434 recruits were participated in the study, with the participation rate of 78.6 %. The results shown that the prevalence of hand dermatitis between April 2007 to April 2008 was 13.4 %. Female were more often affected than male (8.% and 14.6% respectively) and most frequence in young cleaners with age ≤ 30 years (17.9%) and shorter duration of work. Factors which were statistical significantly associated with hand dermatitis were history of atopy, family history of atopy, duration for gloves used, and to chemicals exposure such as benzalconium and ethoxylated nonylphenol substance in floor cleanser. However, age, sex, duration of year work, washing and activities after work were not shown significantly relation with hand dermatitis. In conclusion, this study showed that hand dermatitis among cleaners was association with history ayoty, occupational exposure (benzalconium, ethoxylated nonylphenol). Employers and physicians at the workplace these workers should pay attention in the prevention and surveillance of hand dermatitis.